2020
DOI: 10.1111/1750-3841.15139
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of antioxidant peptides from enzymatic hydrolysate of mungbean protein

Abstract: In this study, the antioxidant activity of mungbean protein hydrolysate (MPH) was systematically investigated. MPH was fractionated by ultrafiltration into two major fractions (MPH‐1 <3 kDa, MPH‐2 >3 kDa). Fraction MPH‐1, which exhibited the highest antioxidant activity, was further fractionated by gel column into three fractions (MPH‐1A, MPH‐1B, and MPH‐1C). The antioxidant activity of the MPH‐1B fraction was stronger than that of the other fractions. Eight mungbean peptides (P1–P8) were identified in fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…The peptides induced the translocation of Nrf2 from cytosol to nucleus, and prevented the interaction of Keap1 to Nrf2, allowing Nrf2 to bind to ARE, and activate the expression of genes that code for antioxidant and oxidants-detoxification enzymes (Trx1, TrxR1, GR, NQO1 and SOD1), suggesting that the mechanism of antioxidant effects of the peptides is via Keap1/Nrf2 signaling pathway. [ 161 , 162 ] WGN, AW, RGWYE and GVPFW from mung bean H 2 O 2 -induced oxidative stress in HepG2 cells The peptides protected HepG2 cells from oxidative stress by increasing cellular viability via elevation in antioxidant status (CAT and GSH system) and inhibition of lipid peroxidation (MDA) [ 163 , 164 ] ITTNPYDY and IGWSPLGSL from Myofibrillar protein of chicken breast H 2 O 2 -induced oxidative stress in NIH-3T3 cells Increased the viability of NIH-3T3 cells, inhibited intracellular ROS and lipid peroxidation in H 2 O 2 -induced oxidative stress in NIH-3T3 cells and improved intracellular glutathione concentration and SOD, CAT, GPx and GSH-Tx activities, and prevented apoptosis via inhibition of caspase-3 activation suggesting that the peptides have both antioxidant and cellular protective properties [ 126 ] GLLLPH from corn gluten meal H 2 O 2 -induced oxidative stress in HepG2 cells Enhanced cell viability, inhibited intracellular ROS generation and lipid peroxidation and improved the expression of antioxidant status (SOD, CAT, GSH-Rx, GSH) [ 165 ] EKWAP, EDGPIPP, EARPPHPPIPP, and EARPPHPPIPPAP H 2 O 2 -induced damage on SH-SY5Y cells Increased viability of cells, restored altered mitochondrial membrane permeability, suppressed ROS generation, NO production and lipid peroxidation, all of which suggest antioxidant protection against oxidative stress [ 166 ] GPA from fish skin gelatin protein hydrolysate H 2 O 2 -induced oxidative injury in IPEC-J2 cells Enhanced ARE-luciferase activity to increase the gene expression and protein level of ARE-dependent antioxidant enzymes as well as reducing cellular ROS generation [ 154 ] YPLPSY from Allium tuberosum H 2 O 2 -induced oxidative injury in HEK293T cells Halted intracellular ROS generation, promoted stressed-cell survival and elevated the gene expression of PI3K, Akt, phospho-Akt, mTOR, phospho-mTOR indicating that the cellular protective...…”
Section: Cellular Mechanisms Of Action Of Fdapsmentioning
confidence: 99%
“…The peptides induced the translocation of Nrf2 from cytosol to nucleus, and prevented the interaction of Keap1 to Nrf2, allowing Nrf2 to bind to ARE, and activate the expression of genes that code for antioxidant and oxidants-detoxification enzymes (Trx1, TrxR1, GR, NQO1 and SOD1), suggesting that the mechanism of antioxidant effects of the peptides is via Keap1/Nrf2 signaling pathway. [ 161 , 162 ] WGN, AW, RGWYE and GVPFW from mung bean H 2 O 2 -induced oxidative stress in HepG2 cells The peptides protected HepG2 cells from oxidative stress by increasing cellular viability via elevation in antioxidant status (CAT and GSH system) and inhibition of lipid peroxidation (MDA) [ 163 , 164 ] ITTNPYDY and IGWSPLGSL from Myofibrillar protein of chicken breast H 2 O 2 -induced oxidative stress in NIH-3T3 cells Increased the viability of NIH-3T3 cells, inhibited intracellular ROS and lipid peroxidation in H 2 O 2 -induced oxidative stress in NIH-3T3 cells and improved intracellular glutathione concentration and SOD, CAT, GPx and GSH-Tx activities, and prevented apoptosis via inhibition of caspase-3 activation suggesting that the peptides have both antioxidant and cellular protective properties [ 126 ] GLLLPH from corn gluten meal H 2 O 2 -induced oxidative stress in HepG2 cells Enhanced cell viability, inhibited intracellular ROS generation and lipid peroxidation and improved the expression of antioxidant status (SOD, CAT, GSH-Rx, GSH) [ 165 ] EKWAP, EDGPIPP, EARPPHPPIPP, and EARPPHPPIPPAP H 2 O 2 -induced damage on SH-SY5Y cells Increased viability of cells, restored altered mitochondrial membrane permeability, suppressed ROS generation, NO production and lipid peroxidation, all of which suggest antioxidant protection against oxidative stress [ 166 ] GPA from fish skin gelatin protein hydrolysate H 2 O 2 -induced oxidative injury in IPEC-J2 cells Enhanced ARE-luciferase activity to increase the gene expression and protein level of ARE-dependent antioxidant enzymes as well as reducing cellular ROS generation [ 154 ] YPLPSY from Allium tuberosum H 2 O 2 -induced oxidative injury in HEK293T cells Halted intracellular ROS generation, promoted stressed-cell survival and elevated the gene expression of PI3K, Akt, phospho-Akt, mTOR, phospho-mTOR indicating that the cellular protective...…”
Section: Cellular Mechanisms Of Action Of Fdapsmentioning
confidence: 99%
“…Nowadays, enzymatic hydrolysis has been widely applied in the structural modification of proteins and the preparation of bioactive peptides (Evangelho et al., 2017; Ghribi et al., 2015; Moure et al., 2006). Previous studies have certified that a series of hydrolysates from plant protein, such as soybean, mung bean, black bean, rice, and millet protein hydrolysates, have shown beneficial health effects such as antioxidant, anti‐hypertensive, antibacterial, antifatigue, and immunomodulatory activities (Liu et al., 2018; Xia et al., 2020; Zheng et al., 2019). Moreover, many researchers demonstrated that the hydrolysates and bioactive polypeptides can be used as nutritional resources in the functional food industry (Agrawal et al., 2020; Chang et al, 2020; Yu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BAPs have also been shown to exert antihypertensive properties (Beltrán‐Barrientos et al, 2016; Jakubczyk et al, 2020). BAPs have been produced from varying sources especially plants and specifically legume seeds such as chickpea, lentil, mungbean (Ding et al, 2020; Garcia‐Mora et al, 2017; Ghribi et al, 2015; Sonklin et al, 2020; Xia et al, 2020; Zhang et al, 2011) but there exist only a few reports on pigeon pea (Bravo et al, 2022; Nawaz et al, 2017). Nevertheless, out of the different categories of bioactive peptides, multifunctional peptides with antioxidant and RAS attenuation properties have attracted much attention lately.…”
Section: Introductionmentioning
confidence: 99%